2016
DOI: 10.2494/photopolymer.29.717
|View full text |Cite
|
Sign up to set email alerts
|

Challenges in Development of Sub-10 nm Resist Materials

Abstract: In the sub-10 nm resist processes for the high volume production of semiconductor devices, the suppression of stochastic phenomena is a critical issue. In this study, the resist processes of line-and-space patterns with sub-10 nm half-pitches were calculated by the Monte Carlo method on the basis of the sensitization and reaction mechanisms of chemically amplified extreme ultraviolet (EUV) resists. The effects of thermalization distance and effective reaction radius for deprotection on line edge roughness (LER… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…4,5) The dependence of LER on the half-pitch of line-and-space patterns has been theoretically investigated on the basis of the reaction mechanisms of chemically amplified resists with the parameters of the latest high-performance chemically amplified resists. [6][7][8][9] It was suggested that LER rapidly increases with the reduction in half-pitch in the sub-10 nm resolution region unless the sensitivity is decreased (the exposure dose is increased). Besides LER, the etch resistance of resist films is a serious problem because the resist film thickness should be decreased with the increase in resolution to avoid the resist pattern collapse.…”
Section: Introductionmentioning
confidence: 99%
“…4,5) The dependence of LER on the half-pitch of line-and-space patterns has been theoretically investigated on the basis of the reaction mechanisms of chemically amplified resists with the parameters of the latest high-performance chemically amplified resists. [6][7][8][9] It was suggested that LER rapidly increases with the reduction in half-pitch in the sub-10 nm resolution region unless the sensitivity is decreased (the exposure dose is increased). Besides LER, the etch resistance of resist films is a serious problem because the resist film thickness should be decreased with the increase in resolution to avoid the resist pattern collapse.…”
Section: Introductionmentioning
confidence: 99%
“…Part of them is aimed at optimization of EUV resist composition and processing conditions during the lithography step. In this group of methods such factors as molecular size, protection ratio, PAG diffusion length and concentration are considered for optimization of the photoresist performance [2][3][4][5]. Other techniques for line-edge roughness mitigation rely on the smoothening effect of plasma treatment and ion bombardment [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%